Photocatalytic removal of perfluoroalkyl substances from water and wastewater: Mechanism, kinetics and controlling factors. (December 2017) - Xu, Bentuo; Ahmed, Mohammad Boshir; Zhou, John L.; Altaee, Ali; Wu, Minghong; Xu, Gang
Abstract: This review focuses on heterogeneous photocatalysis of perfluoroalkyl substances (PFAS) which are of worldwide concern as emerging persistent organic contaminants. Heterogeneous photocatalysis is an effective and advanced technology for PFAS removal from water with relatively high efficacy. During photocatalysis, various short chain perfluorocarboxylic acids (PFCA) are produced as intermediates and the efficacy is related to the photo-generated hole (h + ) and photo-generated electron (e − ). PFAS photodegradation in water under UV irradiation is most effective by using In2 O3 as the catalyst, followed by Ga2 O3 and TiO2 . Significantly, modifying the chemical composition or morphology of the catalyst can improve its efficacy for PFAS removal. In2 O3 porous nanoplates were found to have the best performance of 100% PFAS decomposition under UV light with rate constant ( k t ) and half-time ( τ 1/2 ) of 0.158 min −1 and 4.4 min, respectively. Catalysts perform well in acidic solution and increasing temperature to a certain extent. The photocatalytic performance is reduced when treating wastewater due to the presence of dissolved organic matter (DOM), with the catalysts following the order: needle-like Ga2 O3 > In2 O3 > TiO2 . Future studies should focus on the development of novel photocatalysts, and their immobilization and application for PFAS removal in wastewater. Graphical abstract: Highlights: Heterogeneous photocatalysis is an effective technology for PFAS degradation. Photodecomposition of PFAS in water follows the order: In2 O3 > Ga2 O3 > TiO2 . Photocatalysis performs well in acidic medium and increased with temperature. Dissolved organic matter reduces photocatalytic performance in wastewater. In2 O3 nanoplates degrade 100% PFAS under UV light.